Whitham method for the Benjamin-Ono-Burgers equation and dispersive shocks - Matsuno, Y.; Shchesnovich, V. S.; Kamchatnov, A. M.; Kraenkel, R. A. [UNESP] (American Physical Society (APS), 2007)
The Whitham modulation equations for the parameters of a periodic solution are derived using the generalized Lagrangian approach for the case of the damped Benjamin-Ono equation. The structure of the dispersive shock is considered in this method. © 2007 The American Physical Society.